Method for preparing large-volume artificial stone block by directly utilizing slag
By performing two crystallization and crystallization treatments on the high-temperature discharged slag, combined with its own internal heat annealing process, the problems of high energy consumption, insufficient performance and complex processes in the production of slag artificial stones in the existing technology have been solved, and a large amount of Efficient preparation and high added value utilization of volume artificial stone waste.
Patent Information
- Application Number
- CN202411656452.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-11-19
AI Technical Summary
In the prior art, slag artificial stone has high energy consumption, insufficient stone performance and complex preparation process.
By performing the first crystallization of the high-temperature discharged slag or modified slag, a molten slurry containing the first crystal phase is obtained, and then cast in a large-volume mold to perform the second crystallization and crystallization insulation. Finally, slow annealing and cooling is achieved with its own internal heat to prepare large-volume artificial stone waste.
It reduces production energy consumption, improves the mechanical properties of stone, simplifies the process flow, realizes high value-added utilization of slag, and has a high yield rate, which is suitable for construction and decoration fields.
Smart Images

Figure CN119461896A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of comprehensive utilization of metallurgical resources, and in particular to a method for directly utilizing slag to prepare large-volume artificial stone blocks. Background Art
[0002] Metallurgical slag is a high-temperature waste residue discharged during metal smelting. It has a complex composition and contains free heavy metal ions such as manganese, chromium, zinc, nickel, and lead, which are easily diffused into the environment and cause pollution. The country discharges hundreds of millions of tons of slag every year. Such a large amount of waste slag not only occupies a large amount of land resources, but also causes great harm to the environment due to the presence of heavy metal elements and sulfides in the waste slag.
[0003] At present, most of the comprehensive utilization of slag is for cold slag that has been slowly cooled or quenched by water. The patent with application number 201310544436.2 proposes a temperature-controlled mold casting process method and equipment for producing cast stone from blast furnace slag, but it requires more tempering agents, and the proportion of tempering agents can reach 20% of the slag mass. This means that more energy consumption is required and the process is more complicated, thereby increasing production costs and making it difficult to achieve large-scale utilization of slag. In order to reduce production costs, the patent with application number 201010293048.8 directly uses the sensible heat of the discharged molten blast furnace slag to melt 0-10mass% tempering agent, and then casts it into shape. However, the products prepared by this technology are mainly used for landscape stones with low mechanical properties requirements. They have poor mechanical properties and low yield. The products prepared by the method in this patent cannot be applied to building materials. The patent with application number 202310775660.6 proposes a method and production equipment for producing cast stone using titanium-containing blast furnace slag, and successfully prepares cast stone with good performance. Although the preparation process does not require the addition of a tempering agent, this method has certain limitations. It is only suitable for titanium-containing blast furnace slag. At the same time, pressure equipment is required during the high-temperature heat treatment process, and the process becomes more complicated and costly. It is also difficult to apply to other smelting slags. The method of using slag to prepare stone in the prior art is to prepare small plates / blocks according to different molds, which increases the heat treatment energy consumption of a single plate / block and makes the production process more complicated. Summary of the invention
[0004] The invention provides a method for directly using slag to prepare large-volume artificial stone blocks, so as to solve the technical problems in the prior art of high energy consumption in the production of slag artificial stones, insufficient stone performance and complex preparation process.
[0005] In order to achieve the above-mentioned invention object, the technical solution provided by the present invention is as follows:
[0006] A method for directly using slag to prepare large-volume artificial stone blocks comprises the following steps:
[0007] S1, cooling the first molten slag discharged from the industrial process at high temperature or the second molten slag after adding a modifier online to perform the first crystallization to obtain a molten slurry containing a first crystal phase;
[0008] S2, casting the molten slurry into a large-volume mold and sending it into a kiln. After the slag solidifies, it is crystallized and kept warm at 870-1050° C. for a second crystallization;
[0009] S3. The kiln temperature is lowered to 750°C at a rate of 0.1-0.17°C / min, and external heating is stopped. Slow annealing and cooling are performed only by the internal heat of the artificial stone block body in the mold to obtain a large-volume artificial stone block product.
[0010] Preferably, the first slag in S1 contains two or more compounds of MnS, Cr2O3, Fe2O3, FeO, MnO, MgO, and TiO2.
[0011] Preferably, the first slag in S1 is one or more of silicon manganese slag, copper slag, lead-zinc slag, and titanium-containing blast furnace slag that precipitates a high-temperature crystalline phase under high-temperature liquid conditions.
[0012] Preferably, the second slag in S1 is a slag that does not have high-temperature crystal phase characteristics.
[0013] Preferably, the amount of the modifier added in S1 is 4-10 wt% of the second slag.
[0014] Preferably, the modifier in S1 is one or more of chromite, ferrochrome slag, rutile sand and soda ash.
[0015] Preferably, the first crystalline phase in S1 is one or more of manganese sulfide, spinel, perovskite, and olivine.
[0016] Preferably, the crystal phase precipitated by the second crystallization in S2 is one or more of pyroxene, orthoclase, olivine, spinel, perovskite, diopside, and anorthite.
[0017] Preferably, the crystallization insulation time in S2 is 5-12 hours.
[0018] Preferably, at least one of the three dimensions of length, width and height of the large-volume artificial stone rough material product in S3 is ≤60 cm, and the smallest dimension is ≥10 cm.
[0019] The large-volume artificial stone blocks prepared by the present invention are subjected to cold processing such as cutting to obtain stone products of different types. The stone products of different types refer to various occasions where natural stones such as granite or marble can be used, including architectural decorative stones, pavement stones for roads, parking lots, swimming pools, stations, squares, sidewalks, communities, etc., as well as large blocks of stones used in the fields of curbstones, sculptures, decorations, roads, rivers, tombstones, etc.
[0020] The method of the present invention is to melt and crystallize the first slag or modified slag with the characteristics of high-temperature crystal phase at high temperature, the temperature of the first crystallization is higher than the temperature of the second crystallization, and then further crystallize at 870-920°C after pouring and solidification, and obtain the relevant products after lowering the temperature. The first precipitated crystal phase here can be judged by directly quenching the first slag or modified slag under high-temperature liquid fluidity conditions and judging whether the water-quenched sample contains precipitated crystal phase. The temperature range between the highest crystallization temperature and the lowest crystallization temperature that can be crystallized during the second crystallization is not less than 100°C. Through crystallization, one or more of pyroxene, orthoclase, olivine, spinel, perovskite, diopside, and anorthite appear in large-volume artificial stone, thereby improving mechanical properties. For some second slags that do not have the characteristics of high-temperature crystal phase, the continued use of metallurgical slag can be achieved by additionally adding a modifier.
[0021] Compared with the prior art, the above technical solution has at least the following beneficial effects:
[0022] Compared with the prior art, the advantages of the present invention are:
[0023] (1) Adding modifiers or relying solely on the slag itself, high-temperature crystallization phases can be generated during the high-temperature melting and cooling process, such as manganese sulfide, spinel, perovskite, olivine and other crystalline minerals. These minerals can be initially and evenly precipitated and act as nucleation agents to ensure uniform crystallization inside the stone. Since no special nucleation process is required, this ensures that the slag can undergo a second crystallization during the continued cooling process, and the entire process has low energy consumption.
[0024] (2) The present invention selects slag or modified slag in a suitable crystallization temperature range to have a larger crystallization range; and selects a suitable size of artificial stone blocks, so that in the subsequent cooling process, the temperature difference between the inside and outside can be controlled within a certain temperature range, which not only ensures that large-volume artificial stones can crystallize both inside and outside, but also ensures that the crystallization is uniform and the internal stress is small, thereby meeting the mechanical requirements of large-volume stones and having a high yield rate.
[0025] (3) Based on the characteristics of large-volume stone, the present invention utilizes the characteristics of relatively small-sized microcrystalline glass or cast stone plates, which have more internal heat. In the annealing process, almost no external heat source is required. After stabilization for 1-3 hours after crystallization, annealing and subsequent cooling can be achieved only by its own internal heat. The annealing process after crystallization is short in time and energy consumption.
[0026] (4) The discharged smelting slag has the characteristic of high temperature sensible heat. The second slag without high temperature crystal phase characteristics can be used to melt the modifier (not exceeding 10wt%) through its own sensible heat. No additional heat is required and the purpose of modification can be achieved. The modified slag can be directly cast into shape to prepare stone blocks, avoiding secondary remelting, greatly reducing energy consumption, and realizing the high added value dual utilization of "slag" and "heat" of the slag.
[0027] (5) According to the characteristics of industrial bulk slag emissions, the slag is used to prepare artificial stone blocks, which are not only larger in volume, simpler in preparation process, more in line with the characteristics of industrial slag discharge, but also lower in energy consumption and cost; it can also be processed according to different usage scenarios and needs, the product has strong adaptability and broad market prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 This is the diffraction pattern of the modified molten silicon-manganese slag after water quenching in Example 1;
[0029] Figure 2 It is the diffraction pattern of the modified slag in Example 1 after solidification in the crystallization range of 900-1050°C;
[0030] Figure 3 This is a photo of the finished stone product after cutting the large-volume slag artificial stone rough material in Example 1;
[0031] Figure 4 This is another photo of a finished stone product after cutting the large-volume slag artificial stone rough material in Example 1;
[0032] Figure 5 This is the diffraction pattern of the molten copper slag after water quenching in Example 2. DETAILED DESCRIPTION
[0033] In order to make the purpose, technical solution and advantages of the embodiment of the present invention clearer, the technical solution of the embodiment of the present invention will be clearly and completely described below in conjunction with the drawings of the embodiment of the present invention. Obviously, the described embodiment is a part of the embodiment of the present invention, not all of the embodiments. Based on the described embodiment of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0034] Example 1
[0035] Using 10t of molten silicon-manganese slag (containing MnS, MnO and MgO, etc., the sum of the three is 9.06 mass%) as raw materials, the modifier chromite (containing 40.5 mass% Cr2O3) with a mass percentage of 4% of the slag is directly added to the slag bag containing 10t of molten silicon-manganese slag, and the modifier is melted by the sensible heat of the slag to obtain a slag with a high-temperature crystallization phase, followed by a bag inversion operation and keeping warm for 15 minutes. The modified molten slag is kept warm for 15 minutes under high-temperature liquid conditions and then water quenched. The water-quenched sample has high-temperature crystallization phase spinel, and the test diagram is as follows Figure 1 After the modified slag solidifies, the crystallization phases of pyroxene and pyroxene mainly exist under the heat treatment conditions of 900~1050℃. The relevant test figures are as follows: Figure 2 . The modified slag after inverted homogenization and heat preservation for 15 minutes was cast into a large-volume mold (length, width and height are 1.50, 0.45 and 0.65m respectively), and then immediately sent into a high-temperature kiln. The kiln heat treatment was set at 900℃ for crystallization and heat preservation for 10h, and then cooled to 750℃ at a cooling rate of 0.17℃ / min, and then the heat source was removed and the stone was allowed to cool naturally in the kiln. Finally, the artificial stone rough material obtained had good performance, strong integrity and excellent cutting performance. The obtained samples were further cut and processed into plates such as Figure 3 and Figure 4 Its water absorption, flexural and compressive strength are 0.19%, 52.24Mpa and 142.78MPa respectively, all meeting the requirements of natural stone standards (GB / T18601-2009).
[0036] Example 2
[0037] The molten copper slag (containing Fe2O3, FeO and MgO, etc., the sum of the three is 40.42 mass%) was directly water quenched under high temperature liquid conditions after 25 minutes of heat preservation. The water-quenched sample contained high temperature crystallization phases of spinel and olivine; after the slag solidified, under the heat treatment conditions of 900~1170℃, secondary crystallization phases of olivine and spinel existed. The relevant test figures are shown in Figure 5 . After the slag was kept warm for 25 minutes, it was cast into a mold (length, width and height were 2.0, 0.35 and 0.50m respectively), and then immediately sent into a high-temperature kiln. The kiln heat treatment was set at 900℃ for crystallization and insulation for 11h, and then cooled to 750℃ at a cooling rate of 0.17℃ / min. The heat source was then removed and the stone was allowed to cool naturally in the kiln. The artificial stone rough material had good performance, strong integrity and excellent cutting performance. The obtained samples were further cut and processed into shape, and their water absorption, flexural and compressive strength were 0.08%, 55.98MPa and 420.38MPa respectively, all meeting the requirements of the natural stone standard (GB / T18601-2009).
[0038] Example 3
[0039] The molten titanium-containing blast furnace slag (containing Fe2O3, FeO, TiO2, etc., with a combined total of 13.69 mass%) was directly water quenched under high-temperature liquid conditions. The water-quenched sample contained high-temperature crystallization phase perovskite; after the slag solidified, the crystallization phases of diopside, pyroxene and perovskite existed under the heat treatment conditions of 870~1100℃. After the slag was kept warm for 6 minutes, it was cast into a mold (length, width and height were 1.5, 0.65 and 0.50m respectively), and then immediately sent to a high-temperature kiln. The kiln heat treatment was set at 870℃ for crystallization and insulation for 10h, and then cooled to 750℃ at a cooling rate of 0.12℃ / min, and then the heat source was removed. The stone relied on its own sensible heat annealing and natural cooling in the kiln, and finally the artificial stone rough material had good performance, strong integrity and excellent cutting performance. The obtained samples were further cut and processed into shapes, and their water absorption, flexural and compressive strength were 0.11%, 42.85MPa and 170.08MPa respectively, all meeting the requirements of the natural stone standard (GB / T18601-2009).
[0040] Example 4
[0041] Using 10t of molten silicon-manganese slag (containing MnS, MnO and MgO, etc., the sum of the three is 9.06 mass%) as raw materials, large-volume molten slag artificial stone was prepared at the silicon-manganese-iron alloy production site. The molten slag was kept warm for 20 minutes and water quenched, and high-temperature crystallization phase manganese sulfide existed in the sample; after the slag solidified, pyroxene and pyroxene crystallization phases existed under the heat treatment conditions of 900~1050℃. After the discharged molten silicon-manganese slag was kept warm for 20 minutes, it was directly cast into a mold (length, width and height were 1.50, 0.45 and 0.65m respectively), and then immediately sent to a high-temperature kiln. The kiln heat treatment was set at 900℃ for crystallization and insulation for 10h, and then cooled to 750℃ at a cooling rate of 0.12℃ / min, and then the heat source was removed. The stone relied on its own sensible heat annealing and natural cooling in the kiln, and finally the artificial stone rough material had good performance, strong integrity and excellent cutting performance. The obtained samples were further cut and processed into shapes, and their water absorption, flexural and compressive strength were 0.24%, 34.45MPa and 110.38MPa respectively, all meeting the requirements of the natural stone standard (GB / T18601-2009).
[0042] Example 5
[0043] 10% of the mass percentage of molten ferrochrome slag (containing 8 mass% of Cr2O3) was added to the molten silicon manganese slag (containing FeO, Fe2O3, MnO and MgO, etc., the sum of the four is 13.79 mass%) as a modifier, and after mixing, it was poured through the tundish and kept warm for 10 minutes. The water-quenched sample of the modified molten slag after being kept warm for 10 minutes under high-temperature liquid conditions contained high-temperature crystallization phases of manganese sulfide and spinel; after the modified slag solidified, under the heat treatment conditions of 920~1050℃, the crystallization phases of pyroxene and pyroxene existed. The modified slag after pouring was cast into a mold (length, width and height were 1.50, 0.45 and 0.65m respectively), and then immediately sent to a high-temperature kiln. The kiln heat treatment was set at 920℃ for crystallization and heat preservation for 10h, then cooled to 750℃ at a cooling rate of 0.10℃ / min, and then the heat source was removed. The stone was annealed by its own sensible heat and cooled naturally in the kiln, and finally the artificial stone rough material had good performance, strong integrity and excellent cutting performance. The obtained samples were further cut and processed into shape, and their water absorption, flexural and compressive strength were 0.09%, 54.69MPa and 310.38MPa respectively, all meeting the requirements of the natural stone standard (GB / T18601-2009).
[0044] Example 6
[0045] Add 9% of rutile sand (containing 92.98% of TiO2) as a modifier to the discharged ironmaking slag (containing Fe2O3, FeO, MgO, etc., with a total of 12.20 mass%). The modified molten slag is kept warm for 12 minutes under high temperature liquid conditions and then water quenched. The water-quenched sample contains high temperature crystallization phase perovskite; after the modified slag solidifies, under the heat treatment conditions of 870~1100℃, the crystallization phases of diopside, anorthite and perovskite exist. The mixed modified slag is poured through the tundish and kept warm for 12 minutes, and then directly cast into a mold (length, width and height are 1.5, 0.45, and 0.50m respectively), and then immediately sent to a high temperature kiln. The kiln heat treatment was set at 870℃ for crystallization and heat preservation for 12h, then cooled to 750℃ at a cooling rate of 0.10℃ / min, and then the heat source was removed. The stone was annealed by its own sensible heat and cooled naturally in the kiln, and finally the artificial stone rough material was obtained with good performance, strong integrity and excellent cutting performance. The obtained samples were further cut and processed into shape, and their water absorption, flexural and compressive strength were 0.09%, 56.25MPa and 268.00MPa respectively, all meeting the requirements of the natural stone standard (GB / T18601-2009).
[0046] Example 7
[0047] The water-quenched sample of molten lead-zinc slag (containing FeO, Fe2O3, MnO and MgO, etc., with a sum of 50.06 mass%) kept in high-temperature liquid state for 10 minutes has high-temperature crystallization phase spinel; after the slag solidifies, under the heat treatment conditions of 900~1100℃, there are crystallization phases of pyroxene, spinel, hematite and hematite. The slag discharged from the slag ditch is cast into a mold (length, width and height are 1.50, 0.15 and 0.60m respectively), and then immediately sent to a high-temperature kiln. The kiln heat treatment is set at 1000℃ for crystallization and heat preservation for 5h, and then cooled to 750℃ at a cooling rate of 0.10℃ / min, and then the heat source is removed. The stone relies on its own sensible heat annealing and natural cooling in the kiln, and finally the artificial stone rough material has good performance, strong integrity and excellent cutting performance. The obtained samples were further cut and processed into shapes, and their water absorption, flexural and compressive strength were 0.05%, 70.65MPa and 435.38MPa respectively, all meeting the requirements of the natural stone standard (GB / T18601-2009).
[0048] Example 8
[0049] Add 4% of soda ash as a modifier to the molten lead slag (containing Fe2O3, FeO and MgO, etc., the sum of the three is 58.14mass%). The modified molten slag is kept warm for 15 minutes under high temperature liquid conditions and then quenched with water. The water-quenched sample has high temperature crystallization phase magnetite (iron spinel); after the modified slag solidifies, under the heat treatment conditions of 900~1150℃, the crystallization phases of olivine, pyroxene and iron spinel exist. After the modified slag is kept warm for 15 minutes on site, it is cast into a mold (length, width and height are 1.5, 0.35 and 1.00m respectively), and then immediately sent to a high temperature kiln. The kiln heat treatment is set at 1050℃ for crystallization and insulation for 8h, and then cooled to 750℃ at a cooling rate of 0.15℃ / min, and then the heat source is removed. The stone is cooled naturally in the kiln to obtain artificial stone rough materials with good performance, strong integrity and excellent cutting performance. The obtained samples were further cut and processed into shapes, and their water absorption, flexural and compressive strength were 0.05%, 59.49 MPa and 487.61 MPa respectively, all meeting the requirements of the natural stone standard (GB / T18601-2009).
[0050] The above are only specific embodiments of the present invention, but the protection scope of the present invention is not limited thereto. The protection scope of the present invention shall be based on the protection scope of the claims.
Claims
1. A method for directly using slag to prepare large-volume artificial stone blocks, characterized in that: The following steps are involved: S1, cooling the first molten slag discharged from the industrial process at high temperature or the second molten slag with the modifier added online to perform the first crystallization to obtain a molten slurry containing the first crystal phase; S2, casting the molten slurry into a large-volume mold and sending it into a kiln. After the slag solidifies, it is crystallized and kept warm at 870-1050° C. for a second crystallization; S3. The kiln temperature is lowered to 750°C at a rate of 0.1-0.17°C / min, and external heating is stopped. Slow annealing and cooling are performed only by the internal heat of the artificial stone block body in the mold to obtain a large-volume artificial stone block product.
2. The method for preparing large-volume artificial stone blocks directly using slag according to claim 1, characterized in that: The first slag in S1 contains two or more compounds of MnS, Cr2O3, Fe2O3, FeO, MnO, MgO, and TiO2.
3. The method for preparing large-volume artificial stone blocks directly using slag according to claim 1, characterized in that: The first slag in S1 is one or more of silicon manganese slag, copper slag, lead-zinc slag, and titanium-containing blast furnace slag that precipitates a high-temperature crystalline phase under high-temperature liquid conditions.
4. The method for preparing large-volume artificial stone blocks directly using slag according to claim 1, characterized in that: The second slag in S1 is a slag that does not have high-temperature crystal phase characteristics.
5. The method for preparing large-volume artificial stone blocks directly using slag according to claim 4, characterized in that: The amount of the modifier added in S1 is 4-10 wt% of the second slag.
6. The method for preparing large-volume artificial stone blocks directly using slag according to claim 5, characterized in that: The modifier described in S1 is one or more of chromite, ferrochrome slag, rutile sand and soda ash.
7. The method for preparing large-volume artificial stone blocks directly using slag according to claim 1, characterized in that: The first crystalline phase in S1 is one or more of manganese sulfide, spinel, perovskite, and olivine.
8. The method for preparing large-volume artificial stone blocks directly using slag according to claim 1, characterized in that: The crystal phase precipitated by the second crystallization in S2 is one or more of pyroxene, orthoclase, olivine, spinel, perovskite, diopside, and anorthite.
9. The method for preparing large-volume artificial stone blocks directly using slag according to claim 1, characterized in that: The crystallization and heat preservation time in S2 is 5-12h.
10. The method for preparing large-volume artificial stone blocks directly using slag according to claim 1, characterized in that: The finished large-volume artificial stone rough material in S3 has a size of at least one of the three dimensions of length, width and height of ≤60 cm, and a size of the smallest dimension of ≥10 cm.
Citation Information
Patent Citations
Controlled-temperature ingot casting process and equipment for producing cast stone from blast furnace slag
CN103601377B
Method for using high-temperature liquid silicon manganese alloy slag as raw material to produce cast stone
CN101559953A
Reduced stone raw material production method utilizing melting slag
CN102249567A
Temperature-controllable mold casting process method and equipment for producing cast stone through blast furnace slag
CN103601377A
Method and equipment for producing cast stone by using titanium-containing blast furnace slag
CN116768496A